(untitled) (Journal of Parents and Teachers, 2026)
Due to the pupils’ lack of interest and the ineffectiveness of traditional methods, the teaching team devised a methodology centred on discovery learning. This programme is structured around worksheets that present groups of words with similar spelling difficulties; this enables pupils to deduce the rule for themselves through observation and comparison.